Comparison and difference in the level of jealousy among married couples in long-distance marriages - Dina Ervina; Bramana Nanditya Putra; Wella Yunistia; Elce Purwandari (Research and Social Study Institute, 2025)
This study aims to describe the level of jealousy among husbands in long-distance marriages, the level of jealousy among wives in long-distance marriages, and to identify whether there is a difference in the level of jealousy between husbands and wives in long-distance marriages. This is a comparative study with a sample size of 90 individuals, consisting of 45 husbands and 45 wives in long-distance marriages. The sampling technique used is purposive sampling. The study measures marital satisfaction, which includes social jealousy, sexual jealousy, family jealousy, and work-related jealousy, developed by White. The findings reveal that: the level of jealousy among husbands in long-distance marriages is generally in the moderate category, with a percentage of 52.10%, the level of jealousy among wives in long-distance marriages is generally in the low category, with a percentage of 46.47%, and there is a significant difference in the level of jealousy between husbands and wives in long-distance marriages, with an F-value of 7.474 and a probability of 0.008, which is less than 0.05.